ANALISIS PERAN AUDIT INTERNAL TERHADAP PENCEGAHAN FRAUD BERDASARKAN LITERATURE REVIEW TERINDEKS SINTA - Safitri, Sari; Firdausi, Qonita; Fitriana, Fitriana; Santoso, Rachmat Agus (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
Fraud is currently a concern for business stakeholders in companies and institutions, many entities are experiencing setbacks and even bankruptcy due to a lack of prevention and discipline regarding actions that can lead to fraud so that public trust in a company decreases. Fraud should be detected and prevented from the start, to avoid the company's credibility and accountability. Therefore, the aim of this research was to find out and comprehensively analyze the role of internal audit in the context of fraud prevention efforts. The research design uses qualitative descriptive analysis using a literature review approach. Data was collected in the form of journals or scientific articles totaling 16 articles from journal provider websites. Based on the results of analysis of 16 Sinta indexed articles for 2019-2024. There are 14 articles which state that internal audit has a role in preventing fraud. This finding is supported by the results of data analysis from several studies which show a positive and significant correlation between the role of internal audit and fraud prevention efforts. Then 2 research articles stated that the role of internal audit did not have a significant influence on fraud prevention efforts